2021
DOI: 10.3390/antiox10020263
|View full text |Cite
|
Sign up to set email alerts
|

Plant-Based Phenolic Molecules as Natural Preservatives in Comminuted Meats: A Review

Abstract: Comminuted meat products are highly susceptible to safety and quality degradation partly because of their large interfacial area in the emulsion. The food industry extensively uses synthetic chemical preservatives to delay that degradation which is caused by microbial growth, enzyme activities and oxidation reactions. However, due to the potential health damage (e.g., cardiovascular diseases, neurodegenerative diseases, cancers among others) synthetic preservatives in meat may cause, consumers are becoming ske… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
60
0
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(67 citation statements)
references
References 102 publications
(82 reference statements)
0
60
0
7
Order By: Relevance
“…Many natural and eco-friendly methodologies for food preservation have been proposed in the last few years, but only limited data are available about the usefulness of most of them under industrial scale conditions, which needs proper attention to satisfy the requirements of the industry as well as the demand of the consumers [226][227][228][229][230]. Consequently, studies about the ability of the reported biopreservative agents to control the development of undesirable microorganisms when applied at the industrial scale are greatly required.…”
Section: Discussionmentioning
confidence: 99%
“…Many natural and eco-friendly methodologies for food preservation have been proposed in the last few years, but only limited data are available about the usefulness of most of them under industrial scale conditions, which needs proper attention to satisfy the requirements of the industry as well as the demand of the consumers [226][227][228][229][230]. Consequently, studies about the ability of the reported biopreservative agents to control the development of undesirable microorganisms when applied at the industrial scale are greatly required.…”
Section: Discussionmentioning
confidence: 99%
“…Herbs and herbal extracts have been used for decades as traditional therapy due to their beneficial impact on cellular mechanisms [ 27 ]. Additionally, the use of herbal extracts as antioxidant products and as food additives and physical food conservatives have become more and more popular during the last few years [ 28 ]. It has been demonstrated that plant extracts and phytoconstituents exert their cell protective effects by scavenging free radicals or by enhancing antioxidant defense in vitro and in vivo [ 29 , 30 , 31 , 32 , 33 , 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been noticed that these compounds exert a potent antioxidant effect, even at small concentrations, in in-vitro conditions, but need comparatively higher concentrations in meat model systems, which may result in bitterness and off-flavor. This could be due to interactions between these phenolic compounds with other meat components, such as muscle protein, lipid and minerals [241,242].…”
Section: Prospects and Challengesmentioning
confidence: 99%
“…A proper extraction protocol is critical for obtaining the desired yield percentages and activities of plant extracts that determine their overall effectiveness and success. The high energy and solvent consumption, associated food-safety hazards due to organic solvent residue and waste, are major concerns among food technologists, to the extent that even brand extracts are being prepared from such green alternative methods [241]. The remnants of toxic solvent in plant extracts make them unsuitable for use in the food industry, so to for the loss of active ingredients due to improper high temperature and storage, change in color and flavor, bitterness, increasing cost of production are some important considerations and various food technologists, and researchers are studying these aspects.…”
Section: Prospects and Challengesmentioning
confidence: 99%